Analisis Debit Rencana Dan Evaluasi Kapasitas Jaringan Drainase Perumahan Pesona Pelangi Residence Kecamatan Moncongloe - Hanna M Singgih; Erni Rante Bungin; Dimas S Palebangan (Paulus Civil Engineering Journal, 2023)
In recent years, Maros Regency has become an area that is often affected by floods, one of the affected locations is the Pesona Pelangi Residence housing, Moncongloe District, Maros Regency. Therefore, a plan discharge analysis and drainage system capacity evaluation need to be carried out to find out whether the channel capacity in the Pesona Pelangi Residence housing is adequate to accommodate the planned discharge. It is hoped that the results of the evaluation can be a reference in solving existing problems. The first step of hydrological analysis is the calculation of the planned flood discharge and calculation on the channel dimensions to determine the existing capacity discharge, then compare the plan discharge with the channel capacity discharge. If the capacity discharge exceeds the planned discharge, then the channel is considered capable and vice versait was found that there were 30 channels that were unable to accommodate the planned discharge. If the capacity discharge exceeds the planned discharge, then the channel is considered capable and vice versa. This study calculates the planned discharge with a 5-year anniversary period using the rational method of modifaction and the Manning equation for the calculation of capacity analysis. Based on the survey, the calculation results for the planned rain (5-year anniversary period) were 175.91 mm and it was also found that as many as 30 channels were unable to accommodate the planned discharge.